90Y-labelled anti-CD22 epratuzumab tetraxetan in adults with refractory or relapsed CD22-positive B-cell acute lymphoblastic leukaemia: a phase 1 dose-escalation study. Issue 3 (March 2015) - Chevallier, Patrice; Eugene, Thomas; Robillard, Nelly; Isnard, Françoise; Nicolini, Franck; Escoffre-Barbe, Martine; Huguet, Françoise; Hunault, Mathilde; Marcais, Antoine; Gaschet, Joelle; Cherel, Michel; Guillaume, Thierry; et al.
Summary: Background: Prognosis of patients with relapsed or refractory acute lymphoblastic leukaemia is poor and new treatments are needed. We aimed to assess the feasibility, tolerability, dosimetry, and efficacy of yttrium-90-labelled anti-CD22 epratuzumab tetraxetan ( 90 Y-DOTA-epratuzumab) radioimmunotherapy in refractory or relapsed CD22-positive B-cell acute lymphoblastic leukaemia in a standard 3 + 3 phase 1 study. Methods: Adults (≥18 years) with relapsed or refractory B-cell acute lymphoblastic leukaemia (with CD22 expression on at least 70% of blast cells) were enrolled at six centres in France. Patients received one cycle of 90 Y-DOTA-epratuzumab on days 1 and 8 (give or take 2 days) successively at one of four dose levels: 2·5 mCi/m 2 (92·5 MBq/m 2 ; level 1), 5·0 mCi/m 2 (185 MBq/m 2 ; level 2), 7·5 mCi/m 2 (277·5 MBq/m 2 ; level 3), and 10·0 mCi/m 2 (370 MBq/m 2 ; level 4). The primary objective was to identify the maximum tolerated dose of 90 Y-DOTA-epratuzumab. We assessed safety during infusions and regularly after radioimmunotherapy over a 6-month period. Analyses included only patients who received radioimmunotherapy. The trial is closed to inclusion and is registered atClinicalTrials.gov, NCT01354457 . Findings: Between Aug 25, 2011, and June 11, 2014, 17 patients (median age 62 years; range 27–77) were treated (five at level 1, three at level 2, three at level 3, and six at level 4). Radioimmunotherapy infusion was overall well tolerated. One dose-limiting toxic effect (aplasia lasting 8 weeks) occurred at level 4, but the maximum tolerated dose was not reached. The most common grade 3–4 adverse events were pancytopenia (one patient at level 2, one at level 3, and six at level 4) and infections (three at level 1, one at level 2, and five at level 4). Interpretation: 90 Y-DOTA-epratuzumab radioimmunotherapy is well tolerated. We recommend the dose of 2 × 10·0 mCi/m 2 1 week apart per cycle for phase 2 studies. Funding: Immunomedics and Direction de la Recherche Clinique of Nantes.